Predictors of recycling behavior: a survey-based study in the city of Sharjah, United Arab Emirates - Suhib AlHaj Ali; Lutfi Kawaf; Islam Masadeh; Zaineh Saffarini; Reem Abdullah; Hiba Barqawi (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - Sharjah is the United Arab Emirates' (UAE) third largest city and third highest waste producer (9.9% of ~26 million in 2012). A total of about ~$1bn has been invested into programs pursuing zero-landfill waste by 100% recycling. Besides infrastructure, assessing knowledge, attitudes and practices (KAP) are needed for effective waste management. The purpose of this study is to examine recycling KAP in Sharjah. Design/methodology/approach - A cross-sectional study, using pilot-tested questionnaires, was conducted among public venues during March and April 2016. A total of 400 residents (18-55 years) were selected via convenience sampling. SPSS-22 was used for analysis. Findings - Mean age [28 years (±9.4)] with 56.5% females. Knowledge level [51.8% (±18.1)]; students reported the highest (53.7%, p = 0.007, 95% CI [51.4-56.1]). 22.9% knew recycling benefits, 31.2% knew how to correctly prepare items. Attitude level 92.6% (±16.5); 51.1% and 46.8% would recycle more with a financial reward or penalty, respectively. 70.4% reported practicing recycling; 16.0% always recycle. Logistic regression model indicated knowledge (OR = 1.013, 95% CI [1.001-1.025]) and attitude (OR = 1.014, 95% CI [1.001-1.028]) as the only significant predictors of recycling practice. Originality/value - This is the first study measuring recycling KAP in the UAE. Results could be starting points for improved local waste management and subsequently reduced public health concerns.